Pendidikan Kewirausahaan melalui Pengembangan Ekonomi Kreatif Sablon Cukil - Aden Wijdan Syarif Zaidan; Junanah Junanah (EL-TARBAWI, 2021)
The background of the service is that the development of the KawruhLumbung Studio is needed so that it can be further developed through theCukil Screen Printing Business. The Cukil screen printing business isconsidered to be important expertise to accommodate creativity and improvethe community's economy, especially young people to not migrate but focuson working to support the progress of Petir Village. The lumbung kawruhstudio has several routine activities, including learning to read and writeJavanese script, learning to dance and a mini library. The various creativepotentials above, on the other hand, can be used as a medium forentrepreneurship education for youth in the area. The purpose of this serviceis to develop the art of Cukil (Cukil screen printing) which is applied to tshirts and bags, and to make it a medium for entrepreneurship education for youth in the area. The results of this service process include young people who have had cut-out screen printing skills through the entrepreneurship education process using the focus group discussion method, workshops andthe practice of screen printing.Keywords: Entrepreneurship education, development, Cukil screenprinting.